Carbon Quantum Dots : Synthesis, Properties and Applications - Jelinek, Raz (Springer International Publishing : Imprint: Springer, 2017)
This book introduces the various aspects of the emerging field of carbon dots. Their structural and physico-chemical properties as well as their current and future potential applications are covered. A special chapter on graphene quantum dots is provided. The reader will also find different synthesis routes for carbon quantum dots.- Resumé vydavatel
Keywords: kvantové tečky; nanověda; nanostruktury; quantum dots; nanoscience; nanostructures; elektronické knihy; monografie; electronic books; monographs